Layanan Kemas Ulang Informasi Berbasis Digital - Alwi Alfiana; Samson CMS (Institut Agama Islam Negeri Salatiga, 2020)
AbstractThe increasing need for information in the present era is a problem for information provider institutions to continue making innovations in order to be able to provide relevant information in an attractive manner. On this basis, this research was conducted by finding out how the development of digital-based information services amidst the incessant information. Where in the current information era, every information institution is required to be able to provide interesting and reliable sources of information and be able to package it in an attractive and easily accepted form. The development of digital-based information services with an attractive method, namely repackaging information is an innovation that can be done. Where the purpose of this study is to determine the form of digital information services and the process in providing good service. The benefits of this research can be used to develop the concept of digital-based information services for libraries. The method used is a qualitative method with a descriptive approach. This method is a method in researching the status of human groups, an object, a set of conditions, a system of thought or a class of events in the present. This type of research data is taken through interviews and direct observation of related institutions, so that data can be obtained. a comprehensive range of variables presented. Data analysis wascarried out through several steps such as preparing data instruments, data collection, data classification, data analysis and drawing conclusions. Data from interviews and observations were analyzed using qualitative methods to the variables used as research subjects. Based on the results of data analysis, it was found that information services could be developed attractively through information repackaging carried out by PDDI - LIPI through information repackaging services, namely industrial trees. AbstrakPengembangan layanan informasi berbasis digital dengan metode yang menarik yaitu kemas ulang informasi. Tujuan penelitian ini adalah untuk mengetahui bentuk dari layanan informasi digital dan prosesnya dalam memberikan pelayanan yang baik. Manfaat penelitian ini dapat digunakan untuk menyusun pengembangan konsep layanan infromasi berbasis digital bagi perpustakaan. Data jenis penelitian ini diambil melalui wawancara dan obeservasi secara langsung terhadap lembaga yang terkait, sehingga dapat diperoleh data yang komprehensif terhadap variabel yang disajikan. Data hasil wawancara dan observasi dianalisa dengan menggunakan metode kualitatif terhadap variable yang dijadikan subjek penelitian. Berdasarkan hasil analisis data ditemukan bahwa layanan informasi dapat dikembangkan secara menarik melalui kemas ulang informasi yang di lakukan PDDI – LIPI melalui layanan kemas ulang informasi yaitu pohon industri. Dalam era informasi ini setiap lembaga informasi dituntut untuk mampu memberikan sumber – sumber informasi yang menarik dan dapat dipercaya serta mampu mengemasnya dalam bentuk yang menarik dan mudah diterima. Peneliti juga menyarankan kepada berbagai lembaga informasi tidak terkecuali perpustakaan yang ada di PDDI – LIPI untuk terus memberikan inovasi dan kreatifitas dalam memberikan layanan informasi.